Omega-3 fatty acid supplementation reduces basal TNFalpha but not toll-like receptor stimulated TNFalpha in full sized and miniature mares - Dinnetz, Joyce Marie (Kansas State University, 2009)
It has been well documented that omega-3 PUFA (n-3 PUFA) can confer a wide variety of health benefits to humans and animals. The current study was designed to evaluate the ability of n-3 PUFA to modulate the innate immune response in two diverse breeds of horses. Ten Quarter Horse and 10 American Miniature Horse mares were assigned to either an n-3 PUFA supplemented or control diet (5 full-sized and 5 miniature mares/treatment) for 56 d. The treatment diet was designed to deliver 64.4 mg/kg BW combined eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) daily. Whole blood (20 mL) was collected via jugular veinipuncture into heparinized tubes on 0 d, 28 d, and 56 d. Serum PUFA analysis was conducted by gas chromatography. Peripheral blood mononuclear cell (PBMC) production of tumor necrosis factor-alpha (TNFalpha) in response to toll-like receptor (TLR) ligands lipopolysaccharide (LPS), flagellin, and lipoteichoic acid (LTA) was estimated using an equine-specific ELISA. Peripheral blood samples from d 56 were also analyzed for total and differential leukocyte counts and subjected to flow cytometric analysis. Body type did not affect basal or TLR stimulated TNFα production. Serum PUFA analysis revealed a decrease in linoleic acid (LA) and substantial increases in arachidonic acid (ARA), EPA, DHA, and docosapentaenoic acid (DPA) at both d 28 and 56 in horses fed n-3 PUFA (P less than 0.0001 for all). Dietary n-3 PUFA supplementation reduced (P less than 0.05) un-stimulated basal, but not TLR stimulated TNFalpha production by PBMC’s. Supplementation with n-3 PUFA did not affect total or differential leukocyte counts, nor selected cell surface markers. These results suggest that n-3 PUFA supplementation in the horse can modify circulating PUFA and alter the inflammatory response by reducing basal TNFalpha production. Furthermore, under conditions of the current study and considering the endpoints evaluated, the American Miniature Horse could potentially be used as a model for full-sized horse breeds.
Keywords: Omega-3 fatty acid; Tumor necrosis factor alpha; Horse; American Miniature Horse; Agriculture, Animal Culture and Nutrition (0475)